Problematika Pembentukan Regulasi Di Indonesia Dalam Hal Perencanaan Pembentukan Regulasi Dengan Perencanaan Pembangunan Daerah - Anggita Yudanti; Wicipto Setiadi (Faculty of Sharia, Islamic State University (UIN) Prof. K.H. Saifuddin Zuhri Purwokerto, Indonesia, 2022)
In the context of development, laws and regulations are also a means to support the realization of development goals. The focus of this research is what makes regulations in Indonesia still problematic and what actions must be taken so that the regulatory planning and the regional development planning can be carried out carefully so as to produce good legal products. The method used in this research is a normative approach. Primary data are collected from legislation while secondary data are from books, journals and legal articles. The data are then analyzed in a qualitative descriptive technique. The results found that legislative planning and development planning are not integrated so that they are not synchronized and harmonious because there is a separation of schemes; there is a tendency for excessive formation of Ministerial regulations; and the weakness of the planning institutions for the formation of Governmental and Presidential Regulations. Efforts to synchronize the planning system between the center and the regions are needed so that the regulations formed run systematically and sustainably.